Atividades didáticas investigativas na formação inicial de professores de química, de física e de biologia - Marques, Jose Francisco Zavaglia (2023)
Investigative activities enable the use of research processes such as developing problems, hypotheses, interpretations, arguments and explanations, communication, among others, to promote a scientific attitude, so that in everyday situations it is possible to make decisions and think about solutions for local and global problems. As a way of providing quality teaching and interaction, it is necessary to think about spaces that provide training actions that allow undergraduate students in initial training time for dialogue, and also to interact, reflect, think and review their conceptions, theories, beliefs and knowledge about the teaching and learning. Thus, using the Educational Design Research (EDR) research methodology, we identified a problem based on the research author's practice, which was: What are the contributions and challenges of implementing investigative activities in the initial training of Natural Sciences teachers? in the context of remote teaching? As a possible solution to the problem, we planned and implemented a teaching project with students from different semesters and courses in Chemistry, Physics, and Biological Sciences at the Federal University of Santa Maria. The activities were structures for working with students and included five Investigative Didactic Activities (ADI), each of which followed an investigative problem, a work plan, a text to be read, and communication of the solution found, always varying the degree of freedom in each ADI. We held 15 meetings, including 8 synchronous, alternating with 7 asynchronous, via the Google Meet platform, together with the material available on the Wix website. The data collected, with the digital portfolio and the ADI report, were analyzed through content analysis and we identified three categories a posteriori in the ADI reports: facts, terms, concepts, and scientific phenomena; use and approach to investigative processes and procedures and the social, environmental and economic impact and three categories in the portfolio, namely reflections and citations, professional development and investigative activity. The categories demonstrate that ADI promoted conceptual issues, learning and doing science, as well as articulating dialogue with social, environmental and economic issues, in addition to the presence of the characteristics of the proposed training action and AI in the analyzed excerpts. The ADI set promoted training actions seeking to establish interactions between academics and other moments with the author researcher, collective work, as well as the deepening of theoretical and practical study of the characteristics of AI. The conditions for implementation brought new challenges to the planning and evaluation of student participation in a period of great uncertainty, fear, and insecurity caused by the pandemic while we sought the most appropriate strategies to carry out training with interaction, interest, and mobilization for investigation.